2001
DOI: 10.1176/appi.ps.52.1.104
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction of Inpatients and Outpatients With Staff, Environment, and Other Patients

Abstract: The study described here compared levels of satisfaction with staff, environment, and other patients among 420 first-time and long-term patients in psychiatric outpatient and inpatient settings. The demographic, clinical, and outcome variables associated with satisfaction were explored. Patient satisfaction was related to quality of life, social functioning, treatment expectations, and one-year psychological and physical prognoses. Perceptions of other patients were significantly more positive among long-term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
57
1
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 8 publications
8
57
1
7
Order By: Relevance
“…The quantitative non-randomised papers (Kohler et al, 2015;Muller et al, 2002;Shiva et al, 2009;Sorgaard, 2007) showed a good level of quality, with all four scoring 75%, although some studies reported a low response rate. Of the quantitative descriptive papers reviewed, nine scored 25% (Berghofer et al, 2001;Brunero et al, 2009;Cleary et al, 2009;Gebhardt et al, 2013;Kelstrup et al, 1993;Middelboe et al, 2001;Prince, 2006;Ruggeri et al, 2003;Soergaard et al, 2008), seven scored 50% (Alexius et al, 2000;Barker et al, 1996;Boydell et al, 2012;Gigantesco et al, 2002;Gjerden, 1997;Howard et al, 2003;Smith et al, 2014;Zendjidjian et al, 2014) and three scored 75% (Kuosmanen et al, 2006;Olusina et al, 2002;Zahid et al, 2010). No quantitative descriptive papers gained marks for sample strategy due to a lack of consideration of sample size.…”
Section: Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The quantitative non-randomised papers (Kohler et al, 2015;Muller et al, 2002;Shiva et al, 2009;Sorgaard, 2007) showed a good level of quality, with all four scoring 75%, although some studies reported a low response rate. Of the quantitative descriptive papers reviewed, nine scored 25% (Berghofer et al, 2001;Brunero et al, 2009;Cleary et al, 2009;Gebhardt et al, 2013;Kelstrup et al, 1993;Middelboe et al, 2001;Prince, 2006;Ruggeri et al, 2003;Soergaard et al, 2008), seven scored 50% (Alexius et al, 2000;Barker et al, 1996;Boydell et al, 2012;Gigantesco et al, 2002;Gjerden, 1997;Howard et al, 2003;Smith et al, 2014;Zendjidjian et al, 2014) and three scored 75% (Kuosmanen et al, 2006;Olusina et al, 2002;Zahid et al, 2010). No quantitative descriptive papers gained marks for sample strategy due to a lack of consideration of sample size.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…The CSQ-8 consists of a range of potential scores from 8 to 32, with higher scores indicating greater satisfaction. For the other studies, satisfaction was either quantified, with scores ranging from 60 to 68%, (Barker et al, 1996;Berghofer et al, 2001;Brunero et al, 2009;Cleary et al, 2009), or categorised, with studies reporting satisfaction to be moderate to high (Middelboe et al, 2001;Muller et al, 2002) or simply 'good' (Zahid et al, 2010).…”
Section: General Satisfactionmentioning
confidence: 99%
“…Gouveia et al (2003) examined the level of satisfaction of inpatients and outpatients and found that the level of satisfaction is higher in inpatients. Similarly, Berghofer,et al (2001) found that patients who spend a longer time in health care facilities have more positive impression than short term patients.Based on the research findings, making improvements especially in quality and also physical, communication, social responsibility factors can obtain loyal patients. It is suggested to adopt different strategies to outpatients and inpatients while implementing these improvements.…”
Section: Findings and Discussionmentioning
confidence: 94%
“…En consonancia con lo hallado en trabajos previos, se aprecia una elevada satisfacción con el comportamiento, actitud y competencia de los profesionales (Berghofer et al, 2001;Biegel et al 1995;Blais et al, 2002;Eytan et al, 2004;Gigantesco et al 2002;Kuosmanen et al, 2006); en cambio, se aprecia poca satisfacción en ambos grupos con la información recibida de los profesionales (Allen et al, 2003;Gigantesco et al 2002;Kuosmanen et al,2006) y con la posibilidad de implicación en el programa de tratamiento (Bhugra et al, 2000;Gigantesco et al, 2002). Proveer de información a pacientes y a familiares resulta crucial y no es éste el primer estudio que habla de su importancia.…”
Section: Discussionunclassified
“…Otros autores, en trabajos anteriores, han mostrado que cuanto mayor es el deterioro social, más se ve afectada su calidad de vida, y esto influye en última instancia en el sentimiento de confianza y satisfacción con el cuidado recibido (Berghofer et al, 2001;Längle et al, 2003;Remnik et al, 2004).…”
Section: Discussionunclassified